Professional negligence in the legal profession / Rozita Shaikh Salleh - Shaikh Salleh, Rozita (Faculty of Law, 1985)
This paper primarily deals with professional negligence in the legal profession. The first chapter is the introduction to the paper. In that chapter, the writer discussed the development of torts of negligence and the reception of English Common Law into Malaysia. The authority for this reception is provided under Section 3 of the Civil Law Act 1956 (Revised 1972). The statute also provides for the limitation of time period for the application of this law. However, inspite of the limitation of time period, English Common Law particularly in torts is followed in Malaysia. The second chapter deals with the legal responsibility of a professional person deriving from a combination of contractual and tortious principle. Chapter three deals with Advocates, public policy and the immunity of the Advocates. In this chapter, the case of Rondel V Worsley, in which the House of Lords decided that a barrister enjoys immunity in professional negligence is discussed. This chapter also features the position of Advocates in Malaysia.